Dietary Control of Inflammation and Resolution - Sears, Barry; Saha, Asish K. (Frontiers in Nutrition, 2021)
The healing of any injury requires a dynamic balance of initiation and resolution of inflammation. This review presents an overview of the various nutrients that can act as signaling agents to modify the metabolic responses essential for the optimal healing of injury-induced inflammation. This review describes a defined nutritional program consisting of an integrated interaction of a calorie-restricted anti-inflammatory diet coupled with adequate levels of omega-3 fatty acids and sufficient levels of dietary polyphenols. Each dietary intervention works in an orchestrated manner to reduce, resolve, and repair the tissue damage caused by any inflammation-inducing injury. The orchestration of these specific nutrients and their signaling metabolites to facilitate healing is termed as the Resolution Response. The final stage of the Resolution Response is the activation of intracellular 5' adenosine monophosphate-activated protein kinase (AMPK), which is necessary to repair tissue damaged by the initial injury-induced inflammation. The dietary optimization of the Resolution Response can be personalized to the individual by using standard blood markers. Once each of those markers is in their appropriate ranges, activation of intracellular AMPK will be facilitated. Finally, we outline how the resulting activation of AMPK will affect a diverse number of other intercellular signaling systems leading to an extended healthspan.